Child-Protection Systems – Polish Perspective - Nitecki, Stanisław Józef (Child-Protection Systems, 2025)
Abstract:The main right of a child is the right to live in a natural family. In this family, actions are taken for the good of the child. This right is sometimes violated and transgressed in social life. This means that the state and its bodies must take over responsibility for the care and upbringing of the child. This responsibility is taken over through the institution of foster care. This care can be implemented in institutional and environmental forms. It is to provide the child with appropriate conditions for development when the natural parents are not or cannot provide care. Foster care is temporary. In the event that the child cannot return to the natural family, domestic or international adoption actions are taken. The childcare system assumes that the child is provided with care by natural or adoptive parents. Unfortunately, this system is not effective. A significant number of children remain in foster care until they reach adulthood. In many cases, longer, until they finish school and complete the process of becoming independent. This system is not efficient. There is a lack of foster families providing care and upbringing for children. The gaps in social infrastructure result from the negligence of the bodies responsible for it. They are a consequence of social changes and the lack of foster families. Negative phenomena in this area force corrective actions to be taken. These actions aim to provide children with proper care and upbringing.Keywords: child, foster care, family, local government, care and educational facility